In vitro and in vivo evaluations of the performance of an indirubin derivative, formulated in four different self-emulsifying drug delivery systems - Heshmati, Nasim; Cheng, Xinlai; Dapat, Else; Sassene, Philip; Eisenbrand, Gerhard; Fricker, Gert; Müllertz, Anette (Journal of pharmacy and pharmacology, 2014)
OBJECTIVES: Anticancer indirubins are poorly soluble in water. Here, digestion of four self-emulsifying drug delivery systems (SEDDS) containing E804 (indirubin-3'-oxime 2,3-dihydroxypropyl ether) was compared by dynamic lipolysis and bioavailability studies. Used lipids were either medium-chain or long-chain glycerides. - METHODS: SEDDS E804 were developed. In-vitro lipolysis was carried out at pH 6.5 (37°C) by adding pancreatic lipase (800 U/ml) and controlling by CaCl2 and NaOH addition. E804 content was quantified in the aqueous micellar phase and precipitate using HPLC. Oral bioavailability was determined in rats. Plasma drug content was determined by liquid chromatography (LC)-mass spectrometry. - KEY FINDINGS: All formulations reserved E804 in the aqueous micellar phase up to 60 min. Precipitation proceeded towards the end of lipolysis up to 45%. Lowest level of precipitation (21%) occurred with long-chain lipids (LC-SEDDS). However, lipolysis was not really discriminative between formulations as the drug mainly stayed in solution. Oral administration of formulations resulted in similar bioavailability of E804 with no significantly different area under the concentration curve. Only medium-chain self-nanoemulsifying drug delivery systems revealed shorter Tmax compared with the other formulations. - CONCLUSION: E804 had a similar performance in four lipid/surfactant systems. All formulations increased the bioavailability of E804 with no significant difference.